EUPHEMISMS IN MOTION: CULTURAL AND PRAGMATIC PERSPECTIVES IN ENGLISH AND UZBEK - Olimova Shakhnigor Olim qizi (Western European Studies, 2025)
This article explores the cultural and pragmatic dimensions of euphemisms in English and Uzbek, highlighting their role as linguistic tools for softening taboo or sensitive concepts. Euphemisms reflect the dynamic interplay of language and culture, with English emphasizing social inclusivity and humor, and Uzbek rooted in religious reverence and collectivism. The study analyzes the formation, lifecycle, and societal implications of euphemisms, focusing on processes of degradation and rehabilitation through cross-linguistic comparisons. Grounded in linguistic theories and cultural analysis, the research reveals how euphemisms shape and mirror societal values. The conclusion emphasizes the transient nature of euphemisms and their significance in navigating social sensitivities, offering rich opportunities for further linguistic and cultural research
Keywords: Euphemism; linguistic evolution; cultural context